Investigating The Drivers and Barriers to MOOC Adoption by Course and Training Institutions - Budiarti Budiarti; Dana Indra Sensuse; Harry Budi Santoso; Deden Sumirat Hidayat; Erisva Hakiki Purwaningsih (Eduvest - Journal of Universal Studies, 2024)
The integration of MOOCs into Course and Training Institutions represents a profound shift in the landscape of education delivery and reception. Despite the substantial potential benefits of MOOCs, the adoption process is intricate. This research delves into the essential factors influencing adoption decisions and explores the unique challenges confronted by both adopters and non-adopters. Employing the TAM and TOE theoretical framework, the study utilizes a mixed-methods approach, combining quantitative analysis with qualitative insights from open-ended questions. The findings underscore the critical role of perceived ease of use (PEOU), emphasizing the importance of user-friendly platforms. Additionally, the study recognizes the pivotal influence of Service Quality, Financial Support, and Government Policy in shaping institutional intentions to embrace MOOCs. A comparative analysis between adopters and non-adopters reveals distinctive challenges for each group. Adopter express concerns regarding inadequate government support and promotional efforts affecting platform access. In contrast, non-adopters highlight the necessity for offline training and underscore government-related support and prioritization challenges impacting MOOC adoption.